2017
DOI: 10.1161/jaha.117.006347
|View full text |Cite|
|
Sign up to set email alerts
|

Trimethylamine‐N‐Oxide Induces Vascular Inflammation by Activating the NLRP3 Inflammasome Through the SIRT3‐SOD2‐mtROS Signaling Pathway

Abstract: BackgroundTrimethylamine‐N‐oxide (TMAO) has recently been identified as a novel and independent risk factor for promoting atherosclerosis through inducing vascular inflammation. However, the exact mechanism is currently unclear. Studies have established a central role of nucleotide‐binding oligomerization domain–like receptor family pyrin domain–containing 3 (NLRP3) inflammasome in the pathogenesis of vascular inflammation. Here, we examined the potential role of the NLRP3 inflammasome in TMAO‐induced vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
299
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(311 citation statements)
references
References 47 publications
(78 reference statements)
11
299
1
Order By: Relevance
“…While the studies show the ability of TMAO to promote atherosclerosis [10,11,17,18,30,31], there are numerous contrasting results [19,[32][33][34][35][36]. Treatment of male Fischer 344 rats by L-carnitine in drinking water for 1 year induced tenfold higher TMAO plasma concentration when compared to the control (2.5 vs. 25.0 μM) [36].…”
Section: Discussion/conclusionmentioning
confidence: 98%
See 2 more Smart Citations
“…While the studies show the ability of TMAO to promote atherosclerosis [10,11,17,18,30,31], there are numerous contrasting results [19,[32][33][34][35][36]. Treatment of male Fischer 344 rats by L-carnitine in drinking water for 1 year induced tenfold higher TMAO plasma concentration when compared to the control (2.5 vs. 25.0 μM) [36].…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Ma et al [18], using human umbilical vein endothelial cells, demonstrated that TMAO up-regulates VCAM-1 expression and promotes monocyte adhesion. In the same human umbilical vein endothelial cells model, TMAO promotes early pathological process of atherosclerosis by accelerating inflammation and triggering oxidative stress [17,30,31].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMAO can affect lipid metabolism causing accumulation of cholesterol in cells and it can also have a direct impact on platelet function, promote an inflammatory response and so on. The effect of the TMAO will accelerate the development of atherosclerosis and the level of plasma TMAO and its associated metabolites are directly proportional to the risk of cardiovascular disease (CVD), which will be pointed out in the following sections …”
Section: Metabolites and Effects Of Gmmentioning
confidence: 99%
“…15 There are also studies showing that TMAO enhanced the platelet reactivity and thrombosis risk and promoted vascular inflammation by activating the NLRP3 inflammasome. 16 Using pyrosequencing to analyse the microbial species of atherosclerotic plaques and intestinal microflora in the same atherosclerotic patients, the results show that several bacteria exist simultaneously, suggesting that bacteria found in the plaque may be derived from intestinal flora. 64 In another study using shotgun sequencing method it was found that atherosclerosis patients were rich in Collinsell, and healthy people were rich in Roseburia and Eubacterium.…”
Section: Atherosclerosismentioning
confidence: 99%